Managerial Capability Training for Village Owned Enterprises (BUMDes) Management - Sugianta Ovinus Ginting; Nasrul Efendi; Aren Halomoan Hutasoit (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Weak managerial BUMDes in Silom-lom Village because most of the personnel in the management structure do not fully work for BUMDes, this condition needs to be overcome because it can hinder the effectiveness of BUMDes in producing optimal performance. Another thing that becomes an obstacle to weak management is related to the uneven level of knowledge of managers and different educational backgrounds so that the perspective and mindset of managers in responding to challenges and opportunities differ from one another. The purpose of this managerial training is an effort to transfer knowledge and managerial skills in managing BUMDes with lectures, discussions and question and answer activities. The implementation stages are carried out by compiling the material, training activities, working on the pre test, presenting the material, and closing with filling out the post test. The results of the evaluation of the activities showed that there was an increase in the understanding of the participants. This can be seen in the statement items 2,3,4,6,7,8, and 10 there is an increase in the score from the pre test results. The statement contains understanding the functions of organizational management, understanding how to implement management knowledge into the organization, Managers are people who are fully responsible for management, are able to compile monthly reports including financial reports, are able to make strategic management better, understand business formats including organizational structure, and understand how to manage teamwork within the organization. With the implementation of this activity, managers gain increased knowledge of managing and developing a business.